Effective swimmer’s action during the grab start technique - Mourão, Luis (2015)
The external forces applied in swimming starts have been often studied, but using direct analysis and simple interpretation data processes. This study aimed to develop a tool for vertical and horizontal force assessment based on the swimmers' propulsive and structural forces (passive forces due to dead weight) applied during the block phase. Four methodological pathways were followed: the experimented fall of a rigid body, the swimmers' inertia effect, the development of a mathematical model to describe the outcome of the rigid body fall and its generalization to include the effects of the inertia, and the experimental swimmers' starting protocol analysed with the inclusion of the developed mathematical tool. The first three methodological steps resulted in the description and computation of the passive force components. At the fourth step, six well-trained swimmers performed three 15 m maximal grab start trials and three-dimensional (3D) kinetic data were obtained using a six degrees of freedom force plate. The passive force contribution to the start performance obtained from the model was subtracted from the experimental force due to the swimmers resulting in the swimmers' active forces. As expected, the swimmers' vertical and horizontal active forces accounted for the maximum variability contribution of the experimental forces. It was found that the active force profile for the vertical and horizontal components resembled one another. These findings should be considered in clarifying the active swimmers' force variability and the respective geometrical profile as indicators to redefine steering strategies.